2013
DOI: 10.1080/02699931.2012.747428
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the role of conditioning and stimulus generalisation in common fears and worries

Abstract: Common and persistent fears may emerge through learning mechanisms such as fear conditioning and generalisation. Although there have been extensive studies of these learning processes in healthy but also psychiatric samples, many of the tasks used to produce conditioning and assess generalisation either use painful and aversive stimuli as the unconditioned stimuli (UCS), or suffer from poor belongingness between the conditioned stimuli and the UCS. Here, we present novel data from a paradigm designed to examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 23 publications
3
16
0
Order By: Relevance
“…Haddad, Xu, Raeder, and Lau (2013) predicted that this CS-US combination might increase belongingness within the CS-US relation and facilitate fear learning and generalization. This "screaming lady" paradigm was tested with a group of healthy young adults.…”
Section: Perceptual Fear Generalizationmentioning
confidence: 99%
“…Haddad, Xu, Raeder, and Lau (2013) predicted that this CS-US combination might increase belongingness within the CS-US relation and facilitate fear learning and generalization. This "screaming lady" paradigm was tested with a group of healthy young adults.…”
Section: Perceptual Fear Generalizationmentioning
confidence: 99%
“…Variants that closely resemble the CSþ evoke more fear than variants that have less in common with the CSþ (e.g. Haddad, Xu, Raeder, & Lau, 2013;Lenaert et al, 2014;Lissek et al, 2010;Lommen, Engelhard, & van den Hout, 2010).…”
Section: Introductionmentioning
confidence: 98%
“…Presenting variable CS+ and CS− durations also has the advantage of being better suited to elicit immediate freezing-like responses by removing temporal sources of learning about the US, which may have been acquired during training. Second, we employed a US consisting of a 90db female scream because previous studies found it sufficiently aversive to influence operant behavior and ethically acceptable for use with a range of conditioning tasks and participants (Britton et al, 2011;Haddad et al, 2014). Finally, in order to definitively ascertain whether or not a CS+ is capable of eliciting freezing-like responses in a VR paradigm such as this, we included an additional novel cue that lacks a prior conditioning history at test and compared suppression obtained with CS+ and CS−.…”
Section: Introductionmentioning
confidence: 99%